Impact of Parenting Style on Clinically Significant Behavioral Problems Among Children Aged 4–11 Years Old After Disaster: A Follow-Up Study of the Great East Japan Earthquake - Miki, Takahiro; Fujiwara, Takeo; Yagi, Junko; Homma, Hiroaki; Mashiko, Hirobumi; Nagao, Keizo; Okuyama, Makiko (Frontiers in Psychiatry, 2019)
Objective: The purpose of this study was to investigate the influence of parenting style on children’s behavior problems after the Great East Japan Earthquake in 2011. Methods: Participants were children exposed to the 2011 disaster at preschool age (n=157). Data were collected from August 2012 to March 2013, and from July 2014 to March 2015 (2 and 4 years, respectively, after the earthquake), thus participants were aged 6 to 10 years when assessed. Parenting style was assessed by caregivers using the Alabama Parenting Questionnaire (APQ), which measures parental involvement, positive parenting, poor monitoring/supervision, inconsistent discipline, and corporal punishment in the second year after the disaster. Behavior problems were assessed by caregivers using the Child Behavior Checklist (CBCL), which identifies internalizing, externalizing, and total problems in the second and third year after the disaster. Results: The results show that corporal punishment in the second year after the disaster had negative influence on CBCL internalizing scale (coefficient: 0.78, 95%CI: 0.12 to 1.45, p=0.023), externalizing scale (coefficient: 0.74, 95%CI: 0.09 to 1.39, p=0.025), and total T score in the third year after the disaster (coefficient: 0.85, 95%CI: 0.16 to 1.55, p=0.016), after adjusted for children’s age, sex, the number of trauma experiences, maternal education, the number of siblings, temporally housing experience, and CBCL each scores in the second year after the disaster. Other parenting style did not affect children’s behavioral problems. Conclusion: The result suggests that inadequate rearing after a natural disaster had negative impact on the behavior problems of the affected children in four years later of the disaster. Specifically, corporal punishment had negative influence on children’s behavior problems.